(untitled) (NTU Journal of Agriculture and Veterinary Science, 2025)
The research aims to measure the effectiveness of the technical and cost-effective economic performance of the owners of lamb breeding and fattening fields in Nineveh Governorate for the production year 2023-2024 by measuring the economic efficiency and its components using the data envelopment analysis (DEA) method, and through it measuring and estimating the surplus and deficit in the amount of feed resources consumed, based on the production function represented by the daily weight gain rate and then the total weight gain in those fields. The research results showed that the technical efficiency reached 95%, the allocative efficiency reached about 75%, and the economic efficiency reached 69%, and that there is a waste in the use of resources by 5%, and that there is a surplus in the use of feed resources, which means that there is a waste in the use of feed resources. Hence, we conclude that there is a gap between technical efficiency and allocative efficiency of about 5%, which may be attributed to the high prices of feed resources, which leads to the lack of optimal use of resources and that there is waste in the use of these resources. The research concluded the necessity of setting a pricing policy for all types of feed and setting a price ceiling that serves its profits and provides them between production seasons and neutralizing black market traders in providing it and establishing feed factories for Ruminants